2019
DOI: 10.3390/s20010155
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Solar Radiation for Tomato Water Requirement Calculation in Chinese-Style Solar Greenhouses Based on Least Mean Squares Filter

Abstract: The area covered by Chinese-style solar greenhouses (CSGs) has been increasing rapidly. However, only a few pyranometers, which are fundamental for solar radiation sensing, have been installed inside CSGs. The lack of solar radiation sensing will bring negative effects in greenhouse cultivation such as over irrigation or under irrigation, and unnecessary power consumption. We aim to provide accurate and low-cost solar radiation estimation methods that are urgently needed. In this paper, a method of estimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These results coincided with previous results showing that the proper droplet size provides more carbohydrate and photochemical energy to speed up nitrate accumulation [64] . The results also revealed that the soluble sugar and protein was low at 15 min of spray interval, it was maximum at 30 min of spray interval and then decreased with increasing the spray intervals under all atomizers [65,66] . The finding of this study concluded that a combination of air-assisted atomizers and 30 min of spray interval could be beneficial to improve the nutritional quality of lettuce.…”
Section: Nutritional Quality Of Lettucementioning
confidence: 86%
“…These results coincided with previous results showing that the proper droplet size provides more carbohydrate and photochemical energy to speed up nitrate accumulation [64] . The results also revealed that the soluble sugar and protein was low at 15 min of spray interval, it was maximum at 30 min of spray interval and then decreased with increasing the spray intervals under all atomizers [65,66] . The finding of this study concluded that a combination of air-assisted atomizers and 30 min of spray interval could be beneficial to improve the nutritional quality of lettuce.…”
Section: Nutritional Quality Of Lettucementioning
confidence: 86%
“…The experiment was carried out in a Liaoshen Type III solar greenhouse built in an east-west orientation. The greenhouse was 60 m long and 12 m wide [19]. The heights of the northern wall and northern roof were 3 and 5.5 m, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental control is a key factor to increase plant productivity in controlled environment agriculture (CEA) [1]. Recently, increased interest has been directed towards plant production in closed facilities (e.g., plant factories, vertical farms, indoor-growing modules) [2][3][4]. However, with the introduction of advanced monitoring and control technologies, it becomes necessary to properly discern plant/microclimate interaction, modulate environmental parameters, and manage cultivation factors.…”
Section: Introductionmentioning
confidence: 99%